Hadis di Era Digital: Tantangan dan Peluang Penggunaan Teknologi dalam Studi Hadis - Rosyad, Sabilar; Alif, Muhammad (JIA (Jurnal Ilmu Agama), 2023)
Technology has posed a big challenge to the study of hadith, namely that it is easy for fake hadith to appear or those with wrong interpretations and views. This article aims to analyze the challenges that arise in the use of hadith in the digital era and create strategies that utilize technology in the dissemination and understanding of hadith. By using a descriptive-qualitative method, the results of this discussion show that the study of hadith in the digital era has many challenges, such as the spread of fake hadith easily and causing harm. So the use of technology in Hadith studies requires good ethics and strategies in using existing technology. By respecting religious values, maintaining credibility, protecting privacy, and adhering to applicable ethical guidelines, Hadith researchers can utilize technology in a responsible and beneficial way. With the right approach, the use of technology can enhance understanding, research and dissemination of the rich Hadith heritage to Muslims around the world.